SME international performance in Latin America: The role of entrepreneurial and technological capabilities. Issue 1 (20th February 2017) - Bianchi, Constanza; Glavas, Charmaine; Mathews, Shane
Abstract : Purpose: Small- and medium-sized enterprises (SMEs) from emerging markets in Latin America are increasingly engaging in internationalization. Nevertheless, there is limited research into how these firms achieve international performance. The purpose of this paper is to examine managerial and technology-related capabilities and their impact on international performance of SMEs. Design/methodology/approach: Drawing on data from 233 Chilean SMEs, a model is developed and tested using structural equation modeling. Specifically, the model considers the role of international entrepreneurial orientation and internet technology capabilities on SME international performance, taking into account the mediating effect of international entrepreneurial opportunity recognition and technology-related international networks. Findings: Results show that international entrepreneurial opportunity recognition and international networks mediate the relationship between international entrepreneurial orientation and internet technology capabilities on SME international performance. Research limitations/implications: The context for the study is Chile. However, this is an important emerging market in Latin America with a strong focus on SME internationalization. The research design is cross-sectional and so does not allow for any causal claims to be made. Originality/value: This research contributes to the relatively scant but increasing number of empirical studies which investigate the link between internationalization strategy and SME performance in emerging market contexts.